2021
DOI: 10.1149/1945-7111/ac163e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plasma and Thermal Treatment on the Long-term Performance of Vanadium Redox Flow Electrodes – Significance of Surface Structure vs Oxygen Functionalities

Abstract: Graphite felt (GF) electrodes of vanadium redox flow batteries show enhanced performance when thermally treated before their assembly. Thermal treatment works by simultaneously increasing electrode wettability, kinetic activity, and total surface area (TSA). This study examines these performance determining yet inseparable effects, especially considering the electrodes’ long-term operation. We exposed GF electrodes to 5 min plasma treatment, ensuring equal wettability, and thermally treated them in air at 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This is to be expected, as improved mass transport and wettability following thermal treatment and/or the use of flow channels has also been reported in literature. [109][110][111][112] The as-received coal foam appeared to be very hydrophobic (Fig. 5a), which was thought to contribute to the high ohmic resistance seen during electrochemical measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This is to be expected, as improved mass transport and wettability following thermal treatment and/or the use of flow channels has also been reported in literature. [109][110][111][112] The as-received coal foam appeared to be very hydrophobic (Fig. 5a), which was thought to contribute to the high ohmic resistance seen during electrochemical measurements.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 This is typically achieved through thermal and/or acidic treatments, although air plasma and microwave 13 treatments have also been reported. [14][15][16][17][18][19][20][21] In the field of electrochemistry, it is well known that oxides on carbon play a significant role. 22,23 The Fe(CN) 6 required to catalyze the process, the specific chemical nature of these moieties (such as carbonyls, phenolics, lactones, ethers, or carboxylates) is not critical.…”
Section: mentioning
confidence: 99%
“…In addition to thermal annealing, plasma treatments offer an efficient and controlled means to modify the surface chemistry and structure of the electrode. Despite several reports of such treatments for VRFBs, [14][15][16][17][18][19][20][21] only one publication has explored surface modification using plasma for AORFBs, 31 focusing on acidic AORFB, which is not the most common medium for AORFBs. In this latter study, Permatasari et al demonstrated that the electron transfer rate of Tiron A was improved thanks to oxygen functional groups formed by O 2 plasma treatments.…”
Section: mentioning
confidence: 99%
“…In a further study, Greese et al investigated the impact of thermal and plasma treatment of GF on its (long-term) performance in VRFBs. [37] They found that a longer temperature treatment at 400 °C under air atmosphere results in a lower initial charge-transfer resistance (R CT ) and that its increase during prolonged stress is also lower. Scanning electron microscopy (SEM) and krypton adsorption were used to identify material and surface changes as a function of the thermal treatment time, whereby a roughening and an increased total surface area were observed.…”
Section: Graphite Felt Electrodesmentioning
confidence: 99%